Depression In The Geriatric Patient - McNab, Brian R. (1978)
This article gives the physician a general overview of depression in the elderly. It indicates a number of general parameters which may help the physician gain a greater understanding of depressive illness and to recognize and help the depressed geriatric patient more effectively.